Everyday Climates: Household Archaeologies and the Politics of Scale - Catherine Kearns (Heritage, 2025)
The small scale is recognized as a necessary rebuttal to macroscalar narratives of climate–society relationships in the past, and archeologists and historians have increasingly turned to advocating smaller and shorter scales of analysis and interpretation, from “microclimates” to interannual droughts and single settlement histories. Such provocations rightly caution against the dangers of oversimplification and determinism in recent planetary or Earth-systems approaches to human history, as well as push scholars to acknowledge human-scale experiences: weather, seasonality, landscape change. When it comes to smaller-scale remains, however, like those of household practices, we often consider them data or proxies that validate larger-scale arguments about societal persistence or economic vulnerability. Yet the material and ideational ways that people in premodern worlds made sense of their surroundings, especially via gendered and class-based rhythms of production and consumption, were deeply entwined in the politics of everyday household life. What would a household archeology of climate entail? In this paper I highlight how households themselves were critical sites of environmental construction, experience and history-making through a selection of examples of archeological work from the Mediterranean. I argue that archeologists can critically rethink themes of persistence and adaptation by taking seriously the scalar constructions and varied politics of domestic life.